Single‐Electron Transfer Reactions in Frustrated and Conventional Silylium Ion/Phosphane Lewis Pairs. Issue 46 (18th October 2018) - Merk, Anastasia; Großekappenberg, Henning; Schmidtmann, Marc; Luecke, Marcel‐Philip; Lorent, Christian; Driess, Matthias; Oestreich, Martin; Klare, Hendrik F. T.; Müller, Thomas
Abstract: Silylium ions undergo a single‐electron reduction with phosphanes, leading to transient silyl radicals and the corresponding stable phosphoniumyl radical cations. As supported by DFT calculations, phosphanes with electron‐rich 2, 6‐disubstituted aryl groups are sufficiently strong reductants to facilitate this single‐electron transfer (SET). Frustration as found in kinetically stabilized triarylsilylium ion/phosphane Lewis pairs is not essential, and silylphosphonium ions, which are generated by conventional Lewis adduct formation of solvent‐stabilized trialkylsilylium ions and phosphanes, engage in the same radical mechanism. The trityl cation, a Lewis acid with a higher electron affinity, even oxidizes trialkylphosphanes, such as t Bu3 P, which does not react with either B(C6 F5 )3 or silylium ions. Abstract : An electron against frustration ! Silylium ions accept an electron from sterically hindered triarylphosphanes, regardless of whether these Lewis acids form a frustrated or a classical Lewis pair with the phosphane Lewis base. The thus‐generated phosphoniumyl radical cations were characterized by EPR and UV/Vis absorption spectroscopy and single‐crystal X‐ray diffraction (see picture).